ENHANCEMENT OF ADVENTITIOUS SHOOT REGENERATION IN SESAME (SESAMUM INDICUM L.) CULTIVAR PROMO KY USING ETHYLENE INHIBITORS - Hussein M. Daffalla and M. M. Khalafalla, Eltayb Abdellatef, Magda M.M. Ahmed, (Journal of Phytology, 2010)
Ethylene produced by tissue, callus and plantlets in closed vessels may lead to abnormal plantlet growth and branching in vitro. Silver nitrate (AgNO3) and Cobalt chloride (CoCl2) are known as ethylene inhibitors. Therefore, the objective of this study was to evaluate the in vitro regeneration capacity of sesame cultivar Promo KY when exposed to culture media containing ethylene inhibitors. A protocol is presented for direct adventitious shoot organogenesis and complete plant regeneration. MS medium enriched with 1.0 mg/L Benzyl adenine (BA) induced adventitious shoot in axenic seedling-derived shoot tips. Addition of ethylene inhibitors AgNO3 (0.5- 5.0 mg/L) enhanced number of shoots from 2.7 to 3.7 shoot/explant as well as shoot length from 1.3 to 2.9 cm . In the case of a medium comprising of MS salts with Naphthyl-Acetic Acid (NAA) 0.05 mg/L, 63 root/explant was observed and root emergence occur after 25 days of culture. Addition of 3.0 mg/L AgNO3 improved root initiation to 79 root/explants and root emerged after 14 days. Addition of 5.0 mg/L CoCl2 increase the root length from 3.5 cm to 17 cm. These promotive effects may result from a reduction in ethylene concentration or inhibition of ethylene action. The results found in this study may be used to improve the multiple shoot and rooting efficiency of Sesame cultivars and possibly of other plant species.